UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN SESEWANUA (Clerodendrum squamatum Vahl.) TERHADAP TIKUS PUTIH (Rattus norvegicus L.) YANG DIINDUKSI KARAGENAN - Suryandari, Syari Sekar; Queljoe, Edwin de; Datu, Olvie S. (PHARMACON, 2021)
ABSTRACTSesewanua (Clerodendrum squamatum Vahl.) has been used empirically as a medicine for fever, to reduce swelling and fractures by the people in North Sulawesi. The content of flavonoids in sesewanua leaves can be potential as an anti-inflammatory. Inflammation is the body's response to tissue damage caused by foreign agents. This study aims to prove the anti-inflammatory activity of 96% ethanol extract of sesewanua leaves with various dose of 18 mg/kg, 36 mg/kg, and 72 mg/kg BW in term of the diameter of oedemâ€™s decrease on the soles of rats' feet induced by 1% carrageenan. The diameter of the oedem thickness is measured by using digital calipers. The results showed that the extract of sesewanua leaves was able to reduce the diameter of oedem. The 18 mg/kg BW dose extract had the largest percentage of oedem inhibition, that is 95.04%. The extracts of various doses of 18 mg/kg, 36 mg/kg, and 72 mg/kg BW had no significant differences with positive controls, diclofenac sodium (Ï â‰¥ 0,05). The conclusion of this study, the ethanol extract of sesewanua leaves has been shown to have anti-inflammatory activity similar to diclofenac sodium. The extract dose of 18 mg/kg BW has the most optimal anti-inflammatory effect.Â Keywords: Sesewanua (Clerodendrum squamatum Vahl.), Anti-inflammatory, Oedem, Carrageenan Â ABSTRAKSesewanua (Clerodendrum squamatum Vahl.) telah digunakan secara empiris sebagai obat demam, penurun bengkak, dan patah tulang oleh masyarakat di Sulawesi Utara. Kandungan flavonoid dalam daun sesewanua dapat berpotensi sebagai antiinflamasi. Inflamasi merupakan respon tubuh terhadap kerusakan jaringan yang disebabkan oleh agen asing. Penelitian ini bertujuan untuk membuktikan aktivitas antiinflamasi ekstrak etanol 96% daun sesewanua dengan variasi dosis 18 mg/kgBB, 36 mg/kgBB, dan 72 mg/kgBB dilihat dari penurunan diameter udem pada telapak kaki tikus yang diinduksi karagenan 1%. Diameter ketebalan udem diukur dengan jangka sorong digital. Hasil penelitian menunjukkan ekstrak daun sesewanua dapat menurunkan diameter udem. Ekstrak dosis 18 mg/kgBB memiliki persentase penghambatan udem terbesar yaitu 95,04%. Ekstrak variasi dosis 18 mg/kgBB, 36 mg/kgBB, dan 72 mg/kgBB memiliki perbedaan tidak bermakna dengan kontrol positif (Ï â‰¥ 0,05) Â Kesimpulan dari penelitian ini, ekstrak etanol daun sesewanua terbukti memiliki aktivitas antiinflamasi yang hampir sama dengan natrium diklofenak. Ekstrak dosis 18 mg/kgBB memiliki efek antiinflamasi yang paling optimal.Â Kata kunci: Sesewanua (Clerodendrum squamatum Vahl.), Antiinflamasi, Udem, Karagenan